bahasa inggris - Qonita Shabira; Baharudin; Yuli Yanti (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to identify and analyze trends in Technological Pedagogical and Content Knowledge (TPACK) research in primary education, while also exploring opportunities for further research development. Using the Systematic Literature Review (SLR) method, 226 relevant publications were found in the Scopus and Publish or Perish databases, with 31 documents from the period 2019-2023 selected and analyzed based on inclusion criteria. The literature review process followed PRISMA guidelines to ensure the quality of results, and the data were analyzed using bibliometric methods with the assistance of VOSviewer 1.6.20 software. The results showed a relatively stable increase in TPACK article publications in primary education, despite a slight decline in 2020 and 2023. Most publications originated from China, Turkey, and the United States, with quantitative and qualitative methods being the most commonly used approaches. The main themes explored included technology integration, teacher training, professional development, and educational technology. Density mapping analysis revealed that content, pedagogical, and technological knowledge remain underexplored in depth, indicating that further research is needed to expand understanding of TPACK application in primary education.